ANALISIS PENGELUARAN PEMERINTAH PROVINSI BALI - Tisnawati, Ni Made (INPUT Jurnal Ekonomi dan Sosial; Vol. 1, No. 2 Februari 2009)
As one of fiscal policy, government expenditure is important factor to increasing the economic development in Province of Bali. In five years, the government expenditure is focused on routine expenditure, which not directly give impact to the public. The Province Bali is still depend to central government and loan. To build a good governance, the public participation is a need. The using of e-government especially among young generation is a strategic way.
Keywords: government expenditure, public participation